Biomarkers of Exocrine Pancreatic Injury in 2 Rat Acute Pancreatitis Models. (January 2014) - Usborne, Amy L.; Smith, Aaron T.; Engle, Steven K.; Watson, David E.; Sullivan, John M.; Walgren, Jennie L.
Consistent, sensitive biomarkers of exocrine pancreatic injury (EPIJ) in animal models and humans have historically represented a poorly met need for investigators and clinicians. Experimental design: Sprague-Dawley CD/International Genetic Standard system (IGS) rats were administered cerulein or cyanohydroxybutene (CHB) to induce EPIJ. Serum samples were taken at time points between 1- and 168-hr postinjection (PI), and rats were sacrificed between 24- and 168-hr PI. Method: We investigated a series of serum-based biomarkers including amylase, lipase, pancreas-enriched microRNAs (miRs) and inflammation biomarkers compared with concurrent hematology and pancreatic histology. Results and Conclusion: Microscopic EPIJ was not associated with consistent changes in hematology or inflammation biomarkers. Increased severity scores for EPIJ correlated with increased amylase and lipase values, although severity of EPIJ did not always correlate with the magnitude of enzyme increases. Microscopic EPIJ was most severe at 24 to 48 hr; increases in miR-216a (32-fold) and miR-375 (23-fold) were present at 24 hr and, along with enzymes, were normalized by 48 hr in the cerulein study. MiRs-216a and 375 were increased by ∼800- and 500-fold, respectively, at 24 hr while miR-375 remained elevated until 72 hr in the CHB study. Impact statement: Pancreas-enriched miRs hold promise as novel serum-based biomarkers for EPIJ.